Distribution Characteristics of Soil Organic Carbon and Active Carbon Components in the Peat Swamp Wetlands of the Altai Mountains, China - Guanghua Miao; Yanhong Li; Chongru Shi (Land)
Peat swamp wetlands, crucial carbon pools in terrestrial ecosystems, significantly impact regional carbon cycling and climate change. In this study, the peat swamp wetland in the Altay Mountains was selected as the research object. In July 2023, soil samples were collected in situ from a depth of 0–80 cm of the peat swamp wetland. Subsequently, the contents of soil organic carbon (SOC), dissolved organic carbon (DOC), particulate organic carbon (POC), and the physicochemical properties of the soil samples were determined. The distribution characteristics of soil organic carbon and its active carbon fractions at different soil depths and their influencing factors were investigated. The results demonstrate that (1) SOC, POC, and DOC concentrations were significantly higher in subsurface layers (20–80 cm) than in those of surface layers (0–20 cm), with SOC and POC peaking at 20–40 cm and DOC predominantly accumulating at 40–80 cm. (2) The concentrations of SOC, POC, and DOC reached minima at 0–10 cm, accounting for 17.25%, 16.91%, and 6.46% of the total 0–80 cm profile, respectively. POC represented 76.46% of SOC throughout the profile. (3) Available phosphorus (AP), total nitrogen (TN), ammonium nitrogen (NH4+N), and soil moisture (SM) accounted for an average of 68.94% of the variation in soil organic carbon and active carbon fractions at a depth of 0–80 cm. Higher levels of soil moisture and total nitrogen content emerged as the primary factors responsible for the reduction in soil organic carbon and active carbon fractions. In shallow soils (0–20 cm), an increase in the content of available phosphorus and ammonium nitrogen contributed to a decline in the soil’s active carbon fraction. Conversely, the situation was reversed in deeper soils. This study thus offers scientific insights into alpine peat bog wetland soil carbon dynamics and environmental responses.